2018
DOI: 10.1016/j.celrep.2018.09.058
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Responsive Metabolite, β-Hydroxybutyrate, Attenuates Hypertension

Abstract: Dietary salt reduction and exercise are lifestyle modifications for salt‐sensitive hypertensives. While exercise has prominent metabolic effects, salt has an adverse effect on metabolic syndrome, of which hypertension is a hallmark. We hypothesized that dietary salt impacts metabolism in a salt‐sensitive model of hypertension. An untargeted metabolomics approach demonstrates lower circulating levels of the ketone body, beta‐hydroxybutyrate (βOHB), in high salt‐fed hypertensive rats. Despite the high salt intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(93 citation statements)
references
References 87 publications
(99 reference statements)
6
85
1
1
Order By: Relevance
“…This suggests that the mechanism of benefit is likely to be independent of glucose levels and may possibly stem from a reduction in intraglomerular pressure, [11][12][13] with other possible mechanisms presently being studied. [14][15][16][17] Our trial population was also at high risk for cardiovascular outcomes, with cardiovascular death, myocardial infarction, stroke, or hospitalization for heart failure occurring in 13.8% of the population over a median of 2.62 years of follow-up. The significantly lower rates of cardiovascular outcomes, including the composite of cardiovascular death, myocardial infarction, or stroke, in the canagliflozin group in our trial are consistent with those observed with canagliflozin in the CANVAS (Canagliflozin Cardiovascular Assessment Study) Program, 5 despite the smaller differences in glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the mechanism of benefit is likely to be independent of glucose levels and may possibly stem from a reduction in intraglomerular pressure, [11][12][13] with other possible mechanisms presently being studied. [14][15][16][17] Our trial population was also at high risk for cardiovascular outcomes, with cardiovascular death, myocardial infarction, stroke, or hospitalization for heart failure occurring in 13.8% of the population over a median of 2.62 years of follow-up. The significantly lower rates of cardiovascular outcomes, including the composite of cardiovascular death, myocardial infarction, or stroke, in the canagliflozin group in our trial are consistent with those observed with canagliflozin in the CANVAS (Canagliflozin Cardiovascular Assessment Study) Program, 5 despite the smaller differences in glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary administration of the BHB precursor 1,3-butanediol to rats on a high-salt diet reverted blood pressure to values observed in a low salt diet control group. Moreover, administration of 1,3-butanediol reduced the activity of the Nlrp3 inflammasome, a major inductor of the expression of inflammatory factors, such as caspase-1, IL-1β and IL-18 [58].…”
Section: The Protective Role Of β-Hydroxybutyrate In Hypertensionmentioning
confidence: 99%
“…Experiments performed on rats showed that blood pressure raises with salt content in the diet and is reduced under mild ketosis [57,58]. Dietary administration of the BHB precursor 1,3-butanediol to rats on a high-salt diet reverted blood pressure to values observed in a low salt diet control group.…”
Section: The Protective Role Of β-Hydroxybutyrate In Hypertensionmentioning
confidence: 99%
“…Nutritional or pharmacological activation of GPR109A ameliorates inflammation [144]. In salt-sensitive hypertension, nutritional supplementation of β-hydroxybutyrate precursor, 1,3-butanediol, increases the level of β-hydroxybutyrate and attenuates hypertension through repressing the formation of renal NLRP3 inflammasome [145,146]. Moreover, β-hydroxybutyrate receptor (GPR109A) mediates a significant anti-inflammatory role in various diseases, including atherosclerosis [147].…”
Section: Butyrate and Butyrylationmentioning
confidence: 99%